Disaster Related to Mining: Causes, Impact, and Lesson Learned - Sunarti, Euis; Sumarno, Hadi; Nugraha, Dadang Rahmat; Islamia, Intan (TDMRC, Universitas Syiah Kuala, 2017)
This qualitative-descriptive study aimed to analyze the relationship among risk reduction , natural resource management and poverty as part of Sustainability Development Goals (SDGs) indicators. This research is part of a mandate research from government (Penelitian Unggulan Sesuai Mandat Pusat) which raised the case of illegal gold mining (PETI: Penambangan Emas Tanpa Izin) in Merangin Regency, primary and secondary data were being analyzed using content analysis and DPSIR. Results showed that illegal mining along the river moves from upstream to downstream and cause an increase in catastrophic events. Absence of law enforcement and disaster risk reduction contributed to environmental damage and increase the intensity of floods and flash floods. Disaster managers have not even performed disaster risk analysis therefore it is still far to get to its integration with the achievement of SDGs.Keywords: Disaster, integration, risk reduction, SDGs, Merangin